Hypervector Spaces Based on Intersectional Soft Sets - Young Bae Jun; Chul Hwan Park; N. O. Alshehri (Abstract and Applied Analysis)
The notion of int-soft subfields, int-soft algebras over int-soft subfields, and int-soft hypervector spaces are introduced, and their properties and characterizations are considered. In connection with linear transformations, int-soft hypervector spaces are discussed.